The AtMC4 regulates the stem cell homeostasis in Arabidopsis by catalyzing the cleavage of AtLa1 protein in response to environmental hazards. (January 2018) - Huang, Yifeng; Cui, Yuchao; Hou, Xueliang; Huang, Tao
Highlights: Environmental hazards trigger the cytoplasmic-to-nuclear translocation of AtMC4 protein. The AtMC4 protein catalyzes the cleavage of AtLa1 protein in nucleus, resulting the nuclear-to-cytoplasmic translocation of AtLa1 protein. The cleaved AtLa1 protein enhances the translation of WUS protein in cytoplasm, which further regulates the stem cell homeostasis. Abstract: The AtLa1 protein is an RNA binding factor that initiates the translation of WUSCHEL ( WUS ) mRNA in Arabidopsis. The AtLa1 protein can regulate the stem cell homeostasis via the nuclear-to-cytoplasmic translocation in response to environmental hazards. However, the translocation mechanism of AtLa1 protein remains to be elucidated. In the present study, we have explored the role of AtMC4 protein in the subcellular translocation of AtLa1 protein. Our results showed that the AtLa1 protein is a substrate of AtMC4 protein. The AtMC4 protein can interact with AtLa1 protein and catalyze the cleavage of the C-terminal nuclear localization signal peptide of AtLa1 protein. The AtMC4 protein is mainly distributed in the cytoplasm. In the presence of environmental stresses, the cytoplasmic-to-nuclear translocation of AtMC4 protein is enhanced with the result that more AtLa1 protein can be cleaved and transported from nucleus to cytoplasm, where AtLa1 protein further initiates the translation of WUS mRNA. By contrast, knockdown of AtMC4 expression inhibits the nuclear-to-cytoplasmic translocation of AtLa1 protein and the WUS protein translation. Based on these results, we conclude that the AtMC4 protein regulates stem cell homeostasis by catalyzing the cleavage of AtLa1 protein in response to environmental hazards.